2023
DOI: 10.1038/s41588-023-01485-w
|View full text |Cite
|
Sign up to set email alerts
|

GWAS meta-analysis of over 29,000 people with epilepsy identifies 26 risk loci and subtype-specific genetic architecture

Abstract: Epilepsy is a highly heritable disorder affecting over 50 million people worldwide, of which about one-third are resistant to current treatments. Here we report a multi-ancestry genome-wide association study including 29,944 cases, stratified into three broad categories and seven subtypes of epilepsy, and 52,538 controls. We identify 26 genome-wide significant loci, 19 of which are specific to genetic generalized epilepsy (GGE). We implicate 29 likely causal genes underlying these 26 loci. SNP-based heritabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 98 publications
0
14
0
Order By: Relevance
“…Lastly, genetic mosaicism has been increasingly recognized to contribute to phenotypic diversity in human diseases, including epilepsy 49 , 50 . Genetic mosaicism refers to the accumulation of somatic mutations in the genome that arise during the developing stages after gametogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, genetic mosaicism has been increasingly recognized to contribute to phenotypic diversity in human diseases, including epilepsy 49 , 50 . Genetic mosaicism refers to the accumulation of somatic mutations in the genome that arise during the developing stages after gametogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We used summary statistics from the following studies in Supplementary Fig. 12 : ADHD 112 , ALS 113 , Alzheimer’s disease 114 , age of smoking initiation 115 , autism 116 , bipolar disorder (all, type I, and type II) 117 , cigarettes per day 115 , educational attainment 118 , epilepsy (all, focal, generalized) 119 , height 120 , IQ 121 , insomnia 122 , neuroticism 123 , OCD 124 , schizophrenia 22 , PTSD 125 , risk 126 , subjective well-being 127 , smoking cessation 115 , smoking initiation 115 , Tourette’s 128 and ulcerative colitis 129 .…”
Section: Methodsmentioning
confidence: 99%
“…A large genome-wide association study identified 22 “IGE” loci. 10 Complex inheritance underlies many heritable human traits, such as height, but can create an illusion of understanding. Most cases with IGE have no known cause, and attribution to multiple genes is likely in many cases, but remains unproven, and can minimize consideration of other mechanisms.…”
Section: Etiologymentioning
confidence: 99%